Current Fragmented Film Festival and its Impact on the Process of Building Film Industry in Ethiopia - Paulos Aemero (Integrated Journal for Research in Arts and Humanities, 2022)
This study aimed at examining the current film festivals and filmmaking impact on the process of film company building process in Ethiopia. Thus, in this study qualitative research method was employed. Both primary and secondary sources of data were gathered where the primary data was collected through key informant interviews having 19 film maker participants of the film industry, Directors cinematographers including academicians in Ethiopian Universities in the field of film and Theatre Arts. The secondary date was obtained through books, articles and journals. The data was analyzed by using document and thematic analysis techniques. The study found out that limited or independent film festival preparation, frequent coping from western and European film festival ideas, ineffective film production systems, loose producers company unity, lack of government support on the national film festival, an increase in film festival conspiracy, the financial, human and material constraints, acceptability gaps, the issue of departure film making action and disintegration weakened the unity and strength of the Ethiopian film festival as a whole thereby pretention obstacle in the film company building process in Ethiopia. Finally, this study recommended that strong Film company institutions are mandatory to gather crumbled Ethiopian film festivals and strength which will in turn amalgamate film corporation & film company formation process in Ethiopia.